Efficient modeling of phase change material solidification with multidimensional fins. (December 2017) - Pan, Chunjian; Hoenig, Sean; Chen, Chien-Hua; Neti, Sudhakar; Romero, Carlos; Vermaak, Natasha
Highlights: An efficient modeling approach for Phase Change Material (PCM) solidification process in multi-dimensions is developed. Accurate estimations of the solidification time and the heat flux of a finned PCM system are also obtained. This modeling approach will have small computational cost for optimal design of a finned PCM system. Abstract: Phase Change Materials (PCMs) are gaining importance in energy storage applications. Many PCM are poor thermal conductors and thus can gain from the optimal use of appropriate fins. Phase change process is inherently nonlinear in behavior due to the latent heat, thus simulations are usually based on finite difference or finite element approaches, which can be computationally inefficient for optimal design of latent energy storage systems. A novel modeling approach called Layered Thermal Resistance (LTR) model is proposed for the first time in this paper for efficient PCM simulations in multi-dimensions. The LTR model can be coupled with multidimensional fins for PCM-fin structure optimal design. Compared with CFD results, the results by the LTR model are high accurate in estimating the solidification time and the highlight is it has negligible simulation cost. Moreover, accurate heat flux of a finned PCM system is also obtained. The LTR model represents the nonlinear solidification process in a finned latent energy storage structure with analytic equations, thus it has bright applications in PCM heat sink optimization with internal fins.